Analisis Efektivitas Operasional Layanan Les Privat Berbasis Overall Equipment Effectiveness (OEE): Studi Kasus pada Usaha Pendidikan Nonformal - Mutiara Fitridiani; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2026)
This study examines the operational effectiveness of private tutoring services by adapting the Overall Equipment Effectiveness (OEE) concept to the non-formal education sector. Using a descriptive qualitative approach based on a case study, data was collected through observations, schedule documentation, and evaluation records over an operational period. The analysis revealed Availability of 90%, Performance of 89%, and Quality of 90%, resulting in an OEE of 72%. This figure indicates that service effectiveness is quite good but has not yet reached world-class levels (generally around 85% or higher) as recommended by OEE literature adapted for the service and education sectors. The novelty of this study lies in the use of OEE as a data-driven measurement tool in the context of non-formal education services, specifically private tutoring, to encourage evidence-based continuous improvement. The implications of this study provide an evaluative framework and practical recommendations for private tutoring program managers to enhance service quality through systematic and measurable improvements.